WORLD TRENDS IN TECHNOLOGICAL TRANSFORMATION OF THE MACHINE-BUILDING INDUSTRY (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The article analyzes the world trends of technological transformation of machine-building companies. Innovativeprocesses, such as related production, forecasting services and innovative service models, which are increasingly usedin mechanical engineering, have been studied. The use of modern digital technologies in mechanical engineering forpreventing the risks of losing relevance in the market of modern industry has been studied. The impact of the Covid-19pandemic on the introduction of new technologies by major players in the global mechanical engineering market hasbeen analyzed. Technological innovations have created new business models and opportunities for mechanicalengineering companies. Communication and analytics allow you to create a wide range of applications for industrialtechnology. Although the basic principles of mechanical engineering, such as thermodynamics, fluid mechanics andmachine design, still remain in force, the latest technologies are contributing to the rapid development of composites,mechatronics and nanotechnology. These new subject areas, which are the result of modern achievements, have becomea prerequisite for the development of new and promising industries, including artificial intelligence andbiomechatronics. The growing demand for increased production efficiency while minimizing operating costs has led todemand for new and innovative technologies. The author analyzed the pace of introduction of new technologies in theproduction of mechanical engineering in the world based on the number of patents filed in the field of mechanicalengineering in accordance with current patent classifications. The analysis allows to clearly understand whichtechnological trends are most common in the world market of mechanical engineering. Based on the study of theintroduction of new technologies in mechanical engineering and global trends in the industry, the author substantiatesthe feasibility of accepting the need for deglobalization in mechanical engineering as a new norm; optimization ofexisting production facilities, automation and attraction of advanced digital technologies for the establishment of workprocesses; implementation of advanced technologies in mechanical engineering, such as artificial intelligence, Internetof Things, nanoengineering, advanced data analytics, automation of robotic processes, blockchain, robotics, cloudcomputing, virtual and augmented reality, 3D printing, drones, 5G, etc .; raising the qualification level of mechanicalengineering workers.
Keywords: mechanical engineering, automation, artificial intelligence, Industry 4.0, the Fourth Industrial Revolution